2017
DOI: 10.1155/2017/7981513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graded Facetectomy on Lumbar Biomechanics

Abstract: Facetectomy is an important intervention for spinal stenosis but may lead to spinal instability. Biomechanical knowledge for facetectomy can be beneficial when deciding whether fusion is necessary. Therefore, the aim of this study was to investigate the biomechanical effect of different grades of facetectomy. A three-dimensional nonlinear finite element model of L3–L5 was constructed. The mobility of the model and the intradiscal pressure (IDP) of L4-L5 for standing were inside the data from the literature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 30 publications
3
31
1
1
Order By: Relevance
“…A review of recent studies shows that on average, lumbar spine FEMs from L1-L5 based on CT scans contain approximately 140 000 nodes. 9,11,12,32,[43][44][45][46][47][48] To make a comparison of the computation time required by these models to the time required by the CEM presented in this article, the mesh for the CEM was refined to approximately 140 000 nodes, and a pure moment was applied. When the 140 000-node mesh was used, the model took more than 6 times as long to converge on a solution when compared to the case where 35 000 nodes were used (the standard number of nodes used for the studies presented in this article).…”
Section: Advantages Of a Simplified Cemmentioning
confidence: 99%
“…A review of recent studies shows that on average, lumbar spine FEMs from L1-L5 based on CT scans contain approximately 140 000 nodes. 9,11,12,32,[43][44][45][46][47][48] To make a comparison of the computation time required by these models to the time required by the CEM presented in this article, the mesh for the CEM was refined to approximately 140 000 nodes, and a pure moment was applied. When the 140 000-node mesh was used, the model took more than 6 times as long to converge on a solution when compared to the case where 35 000 nodes were used (the standard number of nodes used for the studies presented in this article).…”
Section: Advantages Of a Simplified Cemmentioning
confidence: 99%
“…Therefore, open surgical removal of the inferior 2/3 lamina, inferior articular process, and partially hypertrophic and cohesive superior articular process (it is the decompression range of transforaminal lumbar interbody fusion) is necessary [5]. However, more than 75% of unilateral or bilateral facetectomy can cause iatrogenic instability to the lumbar spine [6][7][8][9]; thus, supplement with lumbar fusion and pedicel screw fixation is necessary for minimizing the potential risk of future instability and deformity.…”
Section: Introductionmentioning
confidence: 99%
“…For foraminoplasty, various range of proportions and portions of facet joints could be removed, depending on the surgical approaches, surgical technique, surgeons and foraminoplasty way. Although many groups 13–16 have investigated the effect of various resection proportion of facet joints on lumbar biomechanics, and reported that lumbar stability was not significantly affected only if the range of graded facetectomy exceeded 50%, there have been few studies comparing the biomechanical behavior of adjacent segments after foraminoplasty was performed on different facet portions.…”
Section: Discussionmentioning
confidence: 99%
“…Erbulut 15 established FE models of graded facetectomy (total left unilateral medial facetectomy, total bilateral facetectomy, 50% unilateral medial facetectomy, and 75% unilateral medial facetectomy) to evaluate the effect on lumbar ROM. In order to get a more comprehensive biomechanical understanding of the environment in the spine after graded facetectomy, Zeng et al 16 . did a further FE study which investigated the biomechanical effect of graded facetectomy on intervertebral ROM, intradiscal pressure, facet joint forces, and maximum von Mises equivalent stresses.…”
Section: Introductionmentioning
confidence: 99%